Latihan Meniup untuk Meningkatkan Kemampuan Pernapasan Anak Tunarungu - Mardhotillah Putri Iskandar; Irdamurni Irdamurni (Universitas Negeri Padang, 2019)
One of important function of breathing mechanism is producing the voice. Some of deaf children have been able to control their respiration well and some have not when they produced a voice or a sound. In the meantime, when we teach an oral to deaf children we need good control of the respiration so the voice or the sound who came out from their mouth can be heard.This research was using the experimental research in the form of single subject research who has design A-B-A. The data of these children will be measured by recording the duration with a stopwatch.This results are analyzed from direction and stability tendencies who have improvement and overlapping data was 0%. So, it can be concluded that blowing exercices can be increasing the respiratory ability of deaf children.